Pesticide Labeling: Physical or Chemical Hazards - Frederick M. Fishel (EDIS)
This document interprets physical or chemical hazards seen on pesticide labels and discusses criteria used in determining the appropriate hazards for the pesticide. Examples of typical statements found on pesticide labels which convey information to the handler of the product are provided. This document is PI-97, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.